The Analysis of Lightning Strikes to MEAs Distribution Lines on Different Impact Positions - P. Sestasombut; A. Ngaopitakkul (My University, 2017)
This paper focuses on behaviour of voltage across insulator when the lightning strikes on different impact positions of Metropolitan Electricity Authority (MEA) 24 kV distribution lines in Thailand. The simulations and analysis are performed using Alternative Transients Program/Electromagnetic Transients Program (ATP/EMTP) to investigate the voltage across insulator. The results indicate that when the lightning strikes to phase conductor or shielding failure occurs, the voltage across insulator where the terminal point is more than the middle point is about 1.5 times. This case, the ground resistance and grounding distance of overhead ground wire (OHGW) is not influential on the voltage across insulator. However, in case the lightning strikes to OHGW, the voltage across insulator where the terminal point is more than the middle point is about 1.2 times and the ground resistance as well as grounding distance of OHGW plays an important role for the voltage across insulator. The analysis shows that when the lightning strikes to the terminal line are considerably more severe than the middle line. Therefore, the lightning protection should be specially considered at the terminal point. The peak current magnitude and the front time lightning current waveform are essential parameters when observing the voltage across insulator. However, the tail time is not an important parameter with regard to the voltage across insulator.
Keywords: Overhead line; Lightning; Emtp; Lightning and Electromagnetic Phenomena